A case study on yield performance by using different types oil palm varieties planted at Ladang Ketengah Jaya Kemaman / Muhammad Najmudin Mazalan - Mazalan, Muhammad Najmudin (Faculty of Plantation and Agrotechnology, 2017)
The case study is to identify the yield performance of different type of oil palm variety which is yangambi, deli x avros, deli x lame, and GH 500. The type of data for this case study is secondary data that will take from the Ladang Ketengah Jaya estate. The variable for this case study is about yield per year. Take the yield about 3 year for used in this case study. The objective of this case study is to study the effect of using different oil palm variety can influence the yield of oil palm in organization. The case study shows that the yield of oil palm is in the average level from 2013-2015 and the best way is using any of the varieties. All variety have their own characteristic such as using high quality planting materials, have highest weight for fresh fruit bunch, have highest for oil to bunch ratio, it also will be resistant from the main disease in oil palm plantation, tolerant to drought season, and height increment per year. In conclusion, to get the highest yield performance in oil palm plantation, we must choose the best way of maintenance to ensure the profitability.